KERJASAMA INDONESIA DENGAN KOREA SELATAN TERKAIT SERTIFIKASI HALAL PRODUK IMPOR. STUDI KASUS : PRODUK IMPOR MAKANAN INSTAN DARI KOREA SELATAN - Intan Anindita Amarylis, (2023)
This study explains how the South Korean government's efforts to obtain halal certification from LPPOM MUI so that food products produced by South Korean companies can carry out import activities to Indonesia by bagging halal certificates and logos on their products. This study was conducted on the basis of a phenomenon that occurred in 2016, when there was a trend called Samyang Challenge which was widely carried out by Youtube users and made demand for products surge in various countries. This led the Indonesian government to pave the way for Samyang Group producers to sell their products in Indonesia. However, this had become a polemic in the community because there were rumors circulating that the instant noodle contained ingredients that were forbidden to Muslims. This is becoming more widespread as a result of the product's lack of halal logos. To resolve this problem, the Indonesian Government through LPPOM MUI decided to cooperate with Ini Halal Korea to issue halal certificates so that the imported products of instant food can be re-operated and accepted among Indonesian people.